Phytochemical and biological studies of Panicum antidotale aerial parts ethanol extract supported by molecular docking study - Imtisal Sarwar; Muhammad Asif; Talha Jamshaid; Malik Saadullah; Hafiz Muhammad Zubair; Mohammad Saleem; Usama Jamshaid; Fadia S. Youssef; Mohamed L. Ashour; Sameh S. Elhady (Frontiers Media S.A., 2024)
Panicum antidotale has traditionally been used as a poultice to alleviate local inflammation and painful diseases. This study aimed to evaluate the anti-inflammatory, wound-healing, analgesic, and antipyretic potential of its ethanol extract (PAAPEE) in vivo for the first time. In vitro antioxidant assays of Panicum antidotale using a 2,2-diphenyl-1-picrylhydrazyl assay revealed that it showed IC50 of 62.50 ± 6.85 μg/mL in contrast to standard, ascorbic acid, that showed IC50 of 85.51 ± 0.38 μg/mL. Administration of PAAPEE at a dose of 500 mg/kg (PAAPEE-500) displayed 78.44% and 75.13% inhibition of paw edema in carrageenen and histamine-induced edema models. respectively, 6 h post-treatment compared to that of the untreated group. Furthermore, it showed 68.78% inhibition of Freund's complete adjuvant-induced edema 21 days after treatment. It reduced the animal's rectal temperature in the yeast-induced fever model to 99.45 during the fourth h post-treatment. It significantly inhibited abnormal writhing by 44% in the acetic acid-induced pain model. PAE-500 also showed enhancement in wound closure by 72.52% with respect to that of the untreated group on the 10th day post-treatment using the excision healing of wound model. Histopathological examination of skin samples confirmed this improvement, showing enhanced tissue architecture with minimal infiltration of inflammatory cells. High-performance liquid chromatography (HPLC) of PAAPEE revealed the presence of quercetin, gallic, p-coumaric, benzoic, chlorogenic, syringic, ferulic, cinnamic, and sinapic acids. Molecular docking of 5-lipoxygenase and glycogen synthase kinase-3 β protein indicated their potential interaction within the active sites of both enzymes. Thus, P. antidotale serves as an effective natural wound-healing, anti-inflammatory, analgesic, and antipyretic agent.